2017
DOI: 10.1021/acs.est.6b05782
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensors for Personal Monitoring and Estimation of Inhaled Traffic-Related Air Pollution: Evaluation of Methods

Abstract: Physical activity and ventilation rates have an effect on an individual's dose and may be important to consider in exposure-response relationships; however, these factors are often ignored in environmental epidemiology studies. The aim of this study was to evaluate methods to estimate the inhaled dose of air pollution and understand variability, in the absence of a true gold standard metric. Five types of methods were identified: (1) methods using (physical) activity types; (2) methods based on energy expendit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 51 publications
0
33
0
2
Order By: Relevance
“…We included these variables as we believe that parents could be more concerned over the health of their children than over their own health; moreover children are more susceptible to air pollution. Participants who were physically active may be inhaling more pollution because of their increased breathing, thus may be more worried about the health effects of air pollution (Dons et al 2017). They may also be more health-conscious in general, hence more worried about air pollution (Tormo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We included these variables as we believe that parents could be more concerned over the health of their children than over their own health; moreover children are more susceptible to air pollution. Participants who were physically active may be inhaling more pollution because of their increased breathing, thus may be more worried about the health effects of air pollution (Dons et al 2017). They may also be more health-conscious in general, hence more worried about air pollution (Tormo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Higher ventilation rates during physical activity result in an increased pollutant dose and deeper penetration of particles into the lungs (4,5). Nevertheless, various health impact assessments have been carried out and reported that the overall benefits of physical activity outweigh the risks of air pollution (6)(7)(8).…”
Section: Introduction / Backgroundmentioning
confidence: 99%
“…Previous findings have suggested that short-term exposure to air pollution might cause cardiovascular failures, increase respiratory hospitalization and oxidative stress damage, while long-term air pollution exposure might cause cardiovascular mortality, cancer, premature death [ 8 ], and asthma [ 9 ]. It is particularly relevant because during aerobic exercise the higher minute ventilation (VE) could lead to a higher inhalation of pollutants [ 5 ], what has been already discussed in previous studies and analyzed with different methods by Dons et al [ 10 ]. One of the first studies directly investigating the association between the increased VE during exercise and air pollutants inhalation was conducted by Panis et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%